2009
DOI: 10.1016/j.pain.2009.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient intravenous ketamine for the treatment of complex regional pain syndrome: A double-blind placebo controlled study

Abstract: Complex regional pain syndrome (CRPS) is a severe chronic pain condition that most often develops following trauma. The pathophysiology of CRPS is not known but both clinical and experimental evidence demonstrate the important of the NMDA receptor and glial activation in its induction and maintenance. Ketamine is the most potent clinically available safe NMDA antagonist that has a well established role in the treatment of acute and chronic pain. This randomized double-blind placebo controlled trial was designe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
243
1
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(276 citation statements)
references
References 56 publications
9
243
1
8
Order By: Relevance
“…The Scwartzman et al [91] randomized, placebo-controlled trial studied the efficacy of ketamine IV infusions at 25 mL/h for 4 h daily for 10 days versus placebo infusions in 19 CPRS patients. At 12 weeks post-treatment, significant decreases in pain in most affected area, burning pain, pain when touched or lightly touched or brushed lightly, overall pain level, as well as decreased nighttime awakening were found in the ketamine group.…”
Section: Literature On Ketamine Use In Complex Regional Pain Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…The Scwartzman et al [91] randomized, placebo-controlled trial studied the efficacy of ketamine IV infusions at 25 mL/h for 4 h daily for 10 days versus placebo infusions in 19 CPRS patients. At 12 weeks post-treatment, significant decreases in pain in most affected area, burning pain, pain when touched or lightly touched or brushed lightly, overall pain level, as well as decreased nighttime awakening were found in the ketamine group.…”
Section: Literature On Ketamine Use In Complex Regional Pain Syndromementioning
confidence: 99%
“…The titration of ketamine infusions has also differed with some studies titrating in set intervals while others titrating to analgesia or feelings of inebriation [54]. Reported durations of intravenous ketamine infusions have also varied from minutes to hours to infusions up to 10 days [11,91].…”
Section: Optimal Dose and Durationmentioning
confidence: 99%
“…Moreover, the ketamine group also produced less TNF-α post-operation. Numerous clinical studies have shown that ketamine possesses significant analgesic properties [9][10][11]. Our own clinical experience using ketamine for treatment-refractory pain has been positive and we have previously reported long-term pain relief in a patient with fibromyalgia [12].…”
Section: Introductionmentioning
confidence: 99%
“…She has been treated with both ketamine and lidocaine infusions for her CRPS. 5,6 The ketamine has shown benefit in terms of decreasing the diffuse erythema and swelling which occur intermittently over her entire body and face. Lidocaine infusions produce some relief of her pain.…”
Section: Introductionmentioning
confidence: 99%